Prediksi Peningkatan Jumlah Pelanggan dengan Simulasi Monte Carlo - Anggraini, Siska Dwi; Nurcahyo, Gunadi Widi (SAFE-Network, 2021)
CV. Tomi Advertising is a business sector that operates in advertising, construction and promotion that has various types of work services such as manufacturing neonboxes, signboards, signboards, banners, mild steel, modif houses, and others. CV. Tomi Advertising was founded in August 1997 with several ups and downs in business so that it can survive until now by establishing cooperation in several areas such as Pekanbaru, Jambi, Riau Islands and Pangkal Pinang. The recording system for the number of customers who came to CV. Tomi Advertising is done manually using a book. So that the recording of the number of subscribers is not well organized. There are some customers who do not fill in the customer arrival book so that the increase in the number of customers from year to year is less effective. The prediction of the number of subscribers is used as a reference to increase the number of subscribers. The prediction of the number of subscribers is a calculation of the level of the number of customers who come at a certain time. The purpose of this study is to predict the increase in the number of customers that occur at CV. Tomi Advertising. Where, data processing carried out by the Monte Carlo method comes from the amount of data from January 2018 to December 2020. Data processing for the number of customers is also applied to the system using the PHP programming language (Hypertext Processor). Based on the simulation, the increase in the number of customers that has been done is getting an average of 72% so that it can make it easier for business managers to make decisions in order to develop a business.